1999
DOI: 10.1128/jvi.73.6.4543-4551.1999
|View full text |Cite
|
Sign up to set email alerts
|

Amino Acid Substitutions Reveal Distinct Functions of Serine 186 of the ZEBRA Protein in Activation of Early Lytic Cycle Genes and Synergy with the Epstein-Barr Virus R Transactivator

Abstract: The ZEBRA protein mediates the switch between the latent and lytic life cycles of Epstein-Barr virus. Z(S186A), a point mutant in ZEBRA’s basic domain in which serine 186 is changed to alanine, is unable to induce expression of lytic cycle mRNAs or proteins from the latent EBV genome even though it retains the ability to activate transcription from reporters bearing known ZEBRA-responsive promoters (A. L. Francis et al., J. Virol. 71:3054–3061, 1997). We now describe three distinct phenotypes of ZEBRA mutants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
16
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(19 citation statements)
references
References 44 publications
3
16
0
Order By: Relevance
“…The distribution of mutations at residue 68 and 76 which were located in the most important subregion for transactivation [Lieberman and Berk, ; Packham et al, ; Lieberman and Berk, ; Flemington et al, ] in lymphomas was different from the other two tumors (EBVaGCs and nasopharyngeal carcinomas) or throat washing samples from healthy donors. In the DNA binding domain AA 186 plays an important role in mediating DNA recognition on the BRLF1 promoter in the context of the latent virus [Francis et al, ]; AA 189 may influence the DNA‐binding efficiency of ZEBRA [Schelcher et al, ]. In this study AAs 186 and 189 were found to be conserved, further verifying their important biological roles.…”
Section: Discussionsupporting
confidence: 71%
“…The distribution of mutations at residue 68 and 76 which were located in the most important subregion for transactivation [Lieberman and Berk, ; Packham et al, ; Lieberman and Berk, ; Flemington et al, ] in lymphomas was different from the other two tumors (EBVaGCs and nasopharyngeal carcinomas) or throat washing samples from healthy donors. In the DNA binding domain AA 186 plays an important role in mediating DNA recognition on the BRLF1 promoter in the context of the latent virus [Francis et al, ]; AA 189 may influence the DNA‐binding efficiency of ZEBRA [Schelcher et al, ]. In this study AAs 186 and 189 were found to be conserved, further verifying their important biological roles.…”
Section: Discussionsupporting
confidence: 71%
“…Additionally, following primary infection involving the salivary gland, EBV remains latent in epithelial cells of the normal salivary gland and periodically becomes reactivated (18). EBV is actively being shed into saliva as free cells and the detection of EBV by PCR in saliva from lymphoproliferative disorders can be a predictor of disease activation (19).…”
Section: Discussionmentioning
confidence: 99%
“…Previous work demonstrated that ZEBRA's serine 186 (S186) is the major contributor to recognition of methylated DNA (12). Upon mutation of this residue to alanine, ZEBRA recognition of methylated DNA is ablated, essentially eliminating its function in activation of the EBV lytic cascade (24). Several crystal structures have attempted to explain ZEBRA's selectivity for methylated DNA.…”
Section: Discussionmentioning
confidence: 99%